Restoration of rostral cerebrospinal fluid flow to solve treatment failure caused by obstruction in long-term intrathecal baclofen administration. (4th March 2021) - Delhaas, Elmar M.; Harhangi, Biswadjiet S.; van Doormaal, Pieter J.; Dinkelaar, Wouter; van Es, Ad C.G.M.; van Assema, Danielle M.E.; Frankema, Sander P.G.; van der Lugt, Aad; Huygen, Frank J.P.M.
Abstract : Objects: We describe five traumatic spinal cord injury (SCI) patients with an intrathecal baclofen administration (ITB) failure caused by a rostral CSF flow obstruction referred to our expert center between January 2014 and January 2019. We discuss the diagnostic workup, rostral CSF flow obstruction as the cause of the ITB failure and treatment. Methods: When we could not determine the cause of the ITB failure through the patient's history, physical spasticity examination, pump readout, absence of fluid in the pump reservoir during aspiration, or plain radiography, we performed pump catheter access port (computed tomography [CT]) myelography. When CT myelography did not reveal the diagnosis, we used scintigraphy. In an obstruction, we aimed for CSF flow restoration. In three cases, we conducted a laminectomy with microsurgical adhesiolysis. In two of these patients, we could not achieve CSF flow restoration; thus, we placed an intradural catheter bypass. Recently, in three patients, we applied a less invasive technique of percutaneous fenestration of the obstruction. Results: In one case, we performed a successful catheter replacement. In another case using surgical adhesiolysis, spasticity control was complete. In two cases, we could obtain improvement with an additional intradural bypass, followed by a percutaneous fenestration of the obstruction, resulting in further improved CSF flow restoration. In one case, percutaneous fenestration was the first line of treatment. In all cases with percutaneous fenestration, we experienced spasticity control. Conclusion: Preliminary results showed that the restoration of rostral CSF flow might result in an effective ITB treatment in patients with an intrathecal obstruction.